Bioremediation of lindane contaminated soil: Exploring the potential of actinobacterial strains. (September 2021) - Usmani, Zeba; Kulp, Maria; Lukk, Tiit
Abstract: Lindane, an organochlorine pesticide, causes detrimental impacts on the environment and human health owing to its high toxicity, low degradation, and bioaccumulation. Its toxic nature can be overcome by biological and eco-friendly approaches involving its degradation and detoxification. The biodegradation of lindane was assessed using actinobacterial species Thermobifida cellulosilytica TB100 ( T. cellulosilytica ), Thermobifida halotolerans DSM 44931 ( T. halotolerans ) and Streptomyces coelicolor A3 ( S. coelicolor ). The degradation conditions of Lindane such as pH, temperature, inoculum volume, glucose concentration and number of days were optimized under broth conditions. Lindane degradation at different concentrations was studied in soil using reverse phase-high performance liquid chromatography over a 30 day period. A bioassay test was performed on seeds of Lactuca sativa (Lettuce) to assess the success of bioremediated soil. Maximum lindane degradation in soil was observed using T. cellulosilytica sp. The degradation trend for different concentrations of lindane using T. halotolerans in sterilized soil was 55 mg kg −1 (82%) ˃ 155 mg kg −1 (75%) ˃ 255 mg kg −1 (70%) after an incubation period of 30 days. Lindane degradation in soil followed the first order reaction kinetics. Phytotoxicity test on seeds of Lactuca sativa showed considerably good vigor index values for the bioremediated sterilized and non-sterilized soil by T. cellulosilytica, T. halotolerans and S. coelicolor in comparison to the contaminated soil without bacteria. This confirms that these actinobacterial species can be implemented in bioaugmentation of contaminated sites to efficiently remediate high lindane concentrations. Graphical abstract: Image 1 Highlights: Lindane degradation ability of actinobacterial strains was evaluated using RP-HPLC. Optimization of lindane degradation was performed under broth conditions. High lindane degradation rates were observed in soil using Thermobifida strains . Phytotoxicity assay of bioremediated soil was performed on Lettuce seeds.